Advances in studying of the pharmacological activities and structure-activity relationships of natural C-glycosylflavonoids - Peng Zeng; Yong Zhang; Chen Pan; Qi Jia; Fujiang Guo; Yiming Li; Weiliang Zhu; Kaixian Chen (Elsevier, 2013)
C-glycosylflavonoids are characterized by a bond between the anomeric carbon of a sugar moiety and the C-6 or C-8 position of a flavonoid A ring. These compounds are widespread in nature and have become the subject of increasing research interest due to their high biological potential. This review focuses on the biological effects of various C-glycosylflavonoids and their structure-activity relationships (SAR) as elucidated over the last 5 years.